A method for preparing an alumina carrier

By adding a low-temperature microsphere expansion agent to the alumina dry adhesive powder, the double-maximum pore structure expansion of the alumina support is solved, and the existing alumina support cannot produce 100-nanometer pores, and the mechanical strength and reaction activity of the catalyst are improved.

CN116474752BActive Publication Date: 2025-03-07CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210038209.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-13
Publication Date
2025-03-07
Estimated Expiration
2042-01-13

AI Technical Summary

Technical Problem

The existing alumina carriers cannot effectively produce 100-nanometer pores, resulting in poor diffusion of asphaltene molecules, causing the catalyst orifice to be blocked, affecting the normal operation of the device.

Method used

By adding a low-temperature microsphere expansion agent to the alumina dry adhesive powder, and using extrusion strip molding and temperature control methods, the bimodal pore structure of the alumina carrier is expanded to form a hundred-nanometer-scale pore channel with good penetration.

Benefits of technology

It realizes the high mechanical strength and good pore structure of the alumina support, is suitable for residual oil hydrogenation reaction, has the characteristics of high demetalization activity and long catalyst life.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a method for preparing an alumina carrier. The method comprises the following steps: mixing alumina dry rubber powder and a microsphere expansion agent uniformly, kneading, molding, drying, and calcining to obtain an alumina carrier; the microsphere expansion agent has a core-shell structure, the shell of which is a thermoplastic acrylic polymer, and the core is a hydrocarbon; the shell temperature limit of the microsphere expansion agent is 80-150°C; the initial volatilization temperature of the hydrocarbon in the core is 70-100°C. The alumina carrier has an adjustable through-bimodal pore structure within a certain range, has a high proportion of 100-nanometer pores, can meet the diffusion requirements of macromolecular substances, and has the characteristics of high demetallization activity and long catalyst life when applied to residual oil hydrogenation reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing an alumina carrier, in particular to a method for preparing an alumina carrier suitable for a hydrogenation catalyst in the petrochemical industry. Background Art

[0002] With the increasing demand for heavy and inferior crude oil and high-quality light fuel oil in the market, inferior heavy oil processing technology has become a key research direction for major oil companies and oil research institutions. Among them, hydroprocessing technology is one of the most effective technical solutions to improve the quality of inferior heavy oil and provide high-quality raw oil for downstream devices, and it has received widespread attention. In the process of residue oil hydrogenation, since the downstream is a heavy oil catalytic cracking unit, there are strict metal content restrictions on the feed oil. Therefore, most of the metal impurities must be removed during the residue oil hydrogenation process. The asphaltene molecules containing metals can reach ten nanometers. Therefore, for the existing alumina carrier, its pores are mainly concentrated between 2 and 12 nm. Therefore, the asphaltene molecules are severely controlled by internal diffusion and are easily concentrated on the outer surface of the catalyst to react, resulting in serious pore blockage, which in turn causes a rapid increase in pressure drop and affects the normal operation of the device. Therefore, the residue oil hydrogenation catalyst is required to have a large number of hundreds of nanometer-level pores suitable for the diffusion reaction of asphaltene molecules.

[0003] The existing macroporous alumina carrier cannot meet the requirement of directly generating pores at the hundred-nanometer level, so it is a good choice to expand the existing alumina carrier to form a pore size distribution with bimodal pores at the ten-nanometer level and the hundred-nanometer level. However, whether a physical pore expander or a chemical pore expander is used, the existing pore expansion means have problems such as low efficiency of the pore expander, the need for a higher proportion of pore expanders, poor penetration of super-large pores, and the formation of ink bottle-shaped pores, which leads to a decrease in the mechanical strength of the catalyst. For example, CN 102861615B discloses a method for preparing an alumina carrier, which uses pseudo-boehmite, an extrusion aid, a chemical pore expander, an ammonium salt, a physical pore expander carbon black powder, and water to mix and knead extruded strips, but the pores formed by thermal decomposition of the ammonium salt and the holes formed by ablation of carbon black have poor penetration and low mechanical strength, and the utilization efficiency of the pore expander is low. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides a method for preparing an alumina carrier. The alumina carrier prepared by the method has a bimodal pore structure with good permeability that is adjustable within a certain range, has a high proportion of 100-nanometer pores, can meet the diffusion requirements of macromolecular substances, and is applied to residual oil hydrogenation reaction with high demetallization activity and long catalyst life.

[0005] The present invention provides a method for preparing an alumina carrier, comprising the following steps:

[0006] The aluminum oxide dry rubber powder and the microsphere expansion agent are uniformly mixed, kneaded, molded, dried and calcined to obtain the aluminum oxide carrier; the microsphere expansion agent is a low-temperature microsphere expansion agent.

[0007] According to the present invention, the microsphere expansion agent has a core-shell structure; the temperature resistance limit of the shell of the microsphere expansion agent is 80-150°C; and the initial volatilization temperature of the hydrocarbon in the core is 70-100°C.

[0008] According to the present invention, the temperature resistance limit of the shell of the microsphere expansion agent is 110-130°C; the initial volatilization temperature of the hydrocarbon in the core is 80-100°C.

[0009] According to the present invention, the shell of the microsphere expansion agent is a thermoplastic acrylic polymer, and the core is a hydrocarbon.

[0010] According to the present invention, the volume fraction of the inner core hydrocarbon volume of the microsphere expansion agent to the outer shell volume is 0.0001% to 0.1%, preferably 0.0002% to 0.001%.

[0011] According to the present invention, the particle size of the microsphere expansion agent is 1 μm to 50 μm, preferably 10 μm to 20 μm.

[0012] According to the present invention, the microsphere expansion agent can be a commercial product or prepared according to the prior art. The commercial product can be Clocell low-temperature foaming microspheres of POLYCHEM Company of the United States. For example, the product models of Clocell low-temperature foaming microspheres of POLYCHEM Company of the United States are 120DU15, 120DU15-2, etc.

[0013] According to the present invention, preferably, the microsphere expansion agent has the following properties: particle size is 10-20 μm; the initial volatilization temperature of the inner core is 85-95° C.; and the temperature resistance limit of the outer shell is 115-130° C.

[0014] According to the present invention, the weight of the added microsphere expansion agent is 2% to 30% of the weight of the aluminum oxide dry rubber powder, preferably 3% to 15%.

[0015] According to the present invention, water, preferably deionized water, is added when the raw materials are mixed; the amount of water added is 70% to 160% of the weight of the aluminum oxide dry rubber powder, preferably 110% to 130%. Water is added together with other raw materials.

[0016] According to the present invention, an extrusion aid can be added to the raw materials, and the extrusion aid is one or more of sesbania powder, cellulose, polyvinyl alcohol, polyacrylamide, methyl cellulose, and hydroxypropyl methyl cellulose; the amount of the extrusion aid added is 1% to 5% by weight of the alumina dry rubber powder, preferably 2% to 4%. The extrusion aid is added together with other raw materials.

[0017] According to the present invention, a peptizing agent can be added to the raw materials, and the peptizing agent is one or more of nitric acid, citric acid, sulfuric acid, acetic acid, and hydrochloric acid, and the amount added is 1% to 5% by weight of the aluminum oxide dry glue powder, preferably 2% to 3%. The peptizing agent is added together with other raw materials.

[0018] According to the present invention, the temperature of the molding process should be controlled to be 10°C to 50°C higher than the initial volatilization temperature of the microsphere expansion agent core, preferably 20°C to 40°C.

[0019] According to the present invention, the temperature of the molding process should be controlled to be 5°C to 40°C higher than the temperature limit of the shell of the microsphere expansion agent, preferably 10°C to 25°C.

[0020] According to the present invention, the molding may be extrusion molding; the molding process should be carried out in a molding device capable of measuring material temperature, cooling, and heating.

[0021] According to the present invention, the pressure during the molding process should be controlled to be 100 kg / cm 2 ~180kg / cm 2 .

[0022] According to the present invention, the drying is carried out at 50-150°C for 1h-5h; and the calcination is carried out at 500-1000°C for 2h-5h, preferably 800-1000°C.

[0023] According to the present invention, the alumina carrier has a through bimodal pore structure, the alumina carrier has a through bimodal pore structure, the pore volume of the alumina carrier is 0.8-1.3 mL / g; the pore volume occupied by pores with a pore diameter of 1-15 nm is 40%-92% of the total pore volume; the pore volume occupied by pores with a pore diameter of 50-900 nm is 5%-59% of the total pore volume.

[0024] According to the present invention, preferably, in the alumina carrier, the pore volume of pores with a pore diameter of 1 to 15 nm accounts for 40% to 75% of the total pore volume; the pore volume of pores with a pore diameter of 50 to 900 nm accounts for 24% to 59% of the total pore volume.

[0025] According to the present invention, in the alumina carrier, the concentration of the macropore distribution with a pore diameter of 50 to 900 nm can be adjusted, for example, the macropore distribution is concentrated in 100 to 700 nm, or in 100 to 250 nm, 120 to 300 nm, 280 to 550 nm or 280 to 700 nm, etc.

[0026] According to the present invention, the specific surface area of ​​the alumina carrier is 50 cm 2 / g~250cm 2 / g, preferably 90cm2 / g~150cm 2 / g.

[0027] According to the present invention, the mechanical strength of the alumina carrier is 10 to 50 N / mm, preferably 10 to 40 N / mm.

[0028] According to the present invention, the shape of the alumina carrier can be a conventional shape in the art, such as a columnar, spherical, ellipsoidal, cylindrical, bar, impeller, toothed ball, clover, four-leaf clover and other special shapes, and holes can be opened on it, and grooves can be provided on the outer surface.

[0029] According to the present invention, when the alumina carrier is used as a residue oil hydrogenation catalyst, the active metal component can be loaded by common means in the art. The active metal is a metal of Group VIB and / or Group VIII, the metal of Group VIB is preferably molybdenum and / or tungsten, and the metal of Group VIII is preferably cobalt and / or nickel. Based on the mass of the carrier, the content of Group VIB metal oxide is 1% to 20%, and the content of Group VIII metal oxide is 0.1% to 8%.

[0030] The residual oil hydrogenation catalyst prepared by the alumina carrier according to the present invention is suitable for treating the following residual oil: Ni+V content is 20-150 ppm. The content is mass content.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] In the present invention, in the molding method of the alumina carrier, a small amount of low-temperature microsphere expansion agent is added to the alumina dry rubber powder, and the microsphere expansion agent is controlled to perform moderate and controllable pore expansion by controlling the appropriate temperature during extrusion molding through the shape limitation of the extruder and the extrusion pressure, thereby obtaining an alumina carrier having both an adjustable through bimodal pore distribution and high mechanical strength. The method of the present invention avoids the problems of large amount of pore expansion agent, poor mechanical strength, poor penetration of super-large pores, and formation of ink bottle-shaped pores when using traditional pore expansion agents to expand the pores to obtain pores of hundreds of nanometers. The alumina expanded by the microsphere expansion agent is particularly suitable for use as a heavy oil hydrogenation catalyst carrier. The hydrogenation catalyst obtained by loading the active metal on the alumina carrier is used in the residual oil hydrogenation reaction, and has the characteristics of high demetallization activity and long catalyst life. DETAILED DESCRIPTION

[0033] The effects and results of the method of the present invention are further described below with reference to the embodiments, but are not limited to the following embodiments.

[0034] In the present invention, the pore volume and pore distribution are measured by mercury intrusion method; the mechanical strength is measured by a particle strength tester; and the specific surface area is measured by BET method.

[0035] The alumina dry glue powder used in the examples and comparative examples of the present invention is macroporous aluminum hydroxide, and its specific surface area is 245m 2 / g, pore volume is 0.89mL / g, and pore diameter is 12.5nm; pore distribution: pore diameters of 1-15nm account for 96.7%, and 16nm-900nm account for 3.3%.

[0036] In the present invention, the microsphere expansion agent of Examples 1, 2, 3, 5, and 6 is Clocell low-temperature foaming microspheres produced by POLYCHEM Company of the United States, model 120DU15, the particle size of this batch is 15 μm, the initial volatilization temperature of the inner core hydrocarbon is 90°C, and the temperature resistance limit value of the outer shell thermoplastic acrylate polymer is 125°C.

[0037] In the present invention, the microsphere expansion agent of Example 4 is Clocell low-temperature foaming microspheres produced by POLYCHEM Company of the United States, model 120DU15-2, the particle size of this batch is 15 μm, the initial volatilization temperature of the core hydrocarbon is 85°C, and the temperature resistance limit value of the outer shell thermoplastic acrylate polymer is 115°C.

[0038] In the present invention, the pressure of the molding process in each example is controlled to be 140 kg / cm 2 .

[0039] In the present invention, the Ni removal rate / % and V removal rate / % of the embodiments and comparative examples are:

[0040] Ni removal rate / %=1-(Ni mass content in produced oil / Ni mass content in raw oil)×100%;

[0041] V removal rate / %=1-(V mass content in the produced oil / V mass content in the raw oil)×100%.

[0042] Example 1

[0043] Weigh 3g of 120DU15 microspheres, the volume fraction of the hydrocarbon core to the volume fraction of the spherical shell of the thermoplastic acrylate polymer is 0.001%. Mix the microspheres with 100g of alumina dry powder and 120g of deionized water and knead them thoroughly. Put the kneaded materials into a high-temperature extruder that can measure the temperature, cool and heat the materials for extrusion molding. The temperature of the molding process is controlled to be 120°C to obtain the alumina wet strips after pore expansion. Dry in an oven at 110°C at normal pressure for 2h, and after drying, calcine at 850°C for 3h to obtain the alumina carrier.

[0044] The pore volume of the alumina carrier is 0.96 mL / g, and the pore volume of pores with a pore diameter of 1 to 15 nm accounts for 80.2% of the total pore volume. The pores with a pore diameter greater than 15 nm are mainly distributed in the range of 120 nm to 300 nm, and the pore volume of pores with a pore diameter of 120 nm to 300 nm accounts for 15.9% of the total pore volume. The mechanical strength of the alumina carrier is 17 N / mm, and the specific surface area is 125 m 2 / g.

[0045] The alumina carrier is impregnated with an impregnation liquid containing active metals to obtain a hydrogenation catalyst. The hydrogenation catalyst contains 5wt% of molybdenum oxide and 2wt% of nickel oxide based on the mass of the carrier.

[0046] The above hydrogenation catalyst was applied to the residual oil hydrogenation reaction. The raw oil properties of the residual oil hydrogenation reaction are shown in Table 1. The hydrogenation reaction conditions are: temperature 380°C, pressure 15MPa, liquid hourly volume space velocity 1h -1 , hydrogen to oil volume ratio 760. The hydrogenation effect is shown in Table 2.

[0047] Example 2

[0048] Weigh 15g of 120DU15 microspheres, the volume fraction of the hydrocarbon core to the volume fraction of the spherical shell of the thermoplastic acrylate polymer is 0.001%. Mix the microspheres with 100g of alumina dry powder and 120g of deionized water and knead them thoroughly. Put the kneaded materials into a high-temperature extruder that can measure the temperature, cool and heat the materials for extrusion molding. The temperature of the molding process is controlled to be 120°C to obtain the alumina wet strips after pore expansion. Dry in an oven at 110°C at normal pressure for 2h, and after drying, calcine at 850°C for 3h to obtain the alumina carrier.

[0049] The pore volume of the alumina carrier is 1.23mL / g, and the pore volume of pores with a pore diameter of 1 to 15nm accounts for 40.1% of the total pore volume. The pores with a pore diameter greater than 15nm are mainly distributed in the range of 120nm to 300nm, and the pore volume of pores with a pore diameter of 120nm to 300nm accounts for 58.1% of the total pore volume. The mechanical strength of the carrier is 10N / mm, and the specific surface area is 95m 2 / g.

[0050] The alumina carrier is impregnated with an impregnation liquid containing active metals to obtain a hydrogenation catalyst. The hydrogenation catalyst contains 5wt% tungsten oxide and 2wt% cobalt oxide based on the mass of the carrier.

[0051] The above hydrogenation catalyst was applied to the residual oil hydrogenation reaction. The raw oil properties and hydrogenation reaction conditions of the residual oil hydrogenation reaction were the same as those in Example 1. The hydrogenation effect is shown in Table 2.

[0052] Example 3

[0053] Weigh 3g of 120DU15 microspheres, the volume fraction of the hydrocarbon core to the volume fraction of the spherical shell of the thermoplastic acrylate polymer is 0.001%. Mix the microspheres with 100g of alumina dry powder and 120g of deionized water and knead them thoroughly. Put the kneaded materials into a high-temperature extruder that can measure the temperature, cool and heat the materials for extrusion molding. The temperature of the molding process is controlled at 140°C to obtain alumina wet strips after pore expansion. Dry in an oven at 110°C at normal pressure for 2h, and after drying, calcine at 850°C for 3h to obtain an alumina carrier.

[0054] The pore volume of the alumina carrier is 0.95 mL / g, and the pore volume of pores with a pore diameter of 1 to 15 nm accounts for 82.1% of the total pore volume. The pores with a pore diameter greater than 15 nm are mainly distributed in the range of 100 nm to 250 nm, and the pore volume of pores with a pore diameter of 100 nm to 250 nm accounts for 15.1% of the total pore volume. The mechanical strength of the carrier is 18 N / mm, and the specific surface area is 130 m 2 / g.

[0055] The alumina carrier is impregnated with an impregnation liquid containing active metals to obtain a hydrogenation catalyst. The hydrogenation catalyst contains 5wt% tungsten oxide and 2wt% nickel oxide based on the mass of the carrier.

[0056] The above hydrogenation catalyst was applied to the residual oil hydrogenation reaction. The raw oil properties and hydrogenation reaction conditions of the residual oil hydrogenation reaction were the same as those in Example 1. The hydrogenation effect is shown in Table 2.

[0057] Example 4

[0058] Weigh 3g of 120DU15-2 microspheres, the volume fraction of the hydrocarbon in the core to the volume fraction of the spherical shell of the thermoplastic acrylate polymer is 0.0002%. Mix the microspheres with 100g of alumina dry powder, 120g of deionized water, 2g of sesbania powder, and 2ml of nitric acid, and knead them thoroughly. Put the kneaded materials into a high-temperature extruder capable of measuring the temperature, cooling, and heating the materials for extrusion molding. The temperature of the molding process is controlled at 125°C, and the alumina wet strips after pore expansion are dried in an oven at 110°C at normal pressure for 2h. After drying, they are calcined at 850°C for 3h to obtain an alumina carrier.

[0059] The pore volume of the alumina carrier is 0.97 mL / g, pores with a pore diameter of 1 to 15 nm account for 80.7%, pores with a pore diameter greater than 15 nm are mainly distributed in the range of 100 nm to 250 nm, and the pore volume of pores with a pore diameter of 100 nm to 250 nm accounts for 14.2% of the total pore volume. The mechanical strength of the carrier is 17 N / mm, and the specific surface area is 130 m 2 / g.

[0060] The alumina carrier is impregnated with an impregnation liquid containing active metals to obtain a hydrogenation catalyst. The hydrogenation catalyst contains 5wt% of molybdenum oxide and 2wt% of cobalt oxide based on the mass of the carrier.

[0061] The above hydrogenation catalyst was applied to the residual oil hydrogenation reaction. The raw oil properties and hydrogenation reaction conditions of the residual oil hydrogenation reaction were the same as those in Example 1. The hydrogenation effect is shown in Table 2.

[0062] Example 5

[0063] Weigh 3g of 120DU15 microspheres, the volume fraction of the hydrocarbon core to the volume fraction of the spherical shell of the thermoplastic acrylate polymer is 0.001%. Mix the microspheres with 100g of alumina dry rubber powder and 120g of deionized water and knead them thoroughly. Put the kneaded materials into a high-temperature extruder capable of measuring, cooling and heating the materials for extrusion molding. The temperature of the molding process is controlled at 130°C, and the alumina wet strips after pore expansion are dried in an oven at 110°C at normal pressure for 2h. After drying, they are calcined at 850°C for 3h to obtain the alumina carrier.

[0064] The pore volume of the alumina carrier is 0.99 mL / g, pores with a pore diameter of 1 to 15 nm account for 65.8%, and pores with a pore diameter greater than 15 nm are mainly distributed in the range of 280 nm to 700 nm, and the pore volume of pores with a pore diameter of 280 nm to 700 nm accounts for 27.3% of the total pore volume. The mechanical strength of the carrier is 13 N / mm, and the specific surface area is 118 m 2 / g.

[0065] The alumina carrier is impregnated with an impregnation liquid containing active metals to obtain a hydrogenation catalyst. The hydrogenation catalyst contains 5wt% of molybdenum oxide and 2wt% of nickel oxide based on the mass of the carrier.

[0066] The above hydrogenation catalyst was applied to the residual oil hydrogenation reaction. The raw oil properties and hydrogenation reaction conditions of the residual oil hydrogenation reaction were the same as those in Example 1. The hydrogenation effect is shown in Table 2.

[0067] Example 6

[0068] Weigh 3g of 120DU15 microspheres, the volume fraction of the hydrocarbon core to the volume fraction of the spherical shell of the thermoplastic acrylate polymer is 0.001%. Mix the microspheres with 100g of alumina dry powder and 120g of deionized water and knead them thoroughly. Put the kneaded materials into a high-temperature extruder capable of measuring, cooling and heating the materials for extrusion molding. The temperature of the molding process is controlled at 150°C, and the alumina wet strips after pore expansion are dried in an oven at 110°C at normal pressure for 2h. After drying, they are calcined at 850°C for 3h to obtain the alumina carrier.

[0069] The pore volume of the alumina carrier is 0.99 mL / g, pores with a pore diameter of 1 to 15 nm account for 68.9%, pores with a pore diameter greater than 15 nm are mainly distributed in the range of 280 nm to 550 nm, and the pore volume of pores with a diameter of 280 nm to 550 nm accounts for 25.1% of the total pore volume. The mechanical strength of the carrier is 15 N / mm, and the specific surface area is 120 m 2 / g.

[0070] The alumina carrier is impregnated with an impregnation liquid containing active metals to obtain a hydrogenation catalyst. The hydrogenation catalyst contains 5wt% of molybdenum oxide and 2wt% of nickel oxide based on the mass of the carrier.

[0071] The above hydrogenation catalyst was applied to the residual oil hydrogenation reaction. The raw oil properties and hydrogenation reaction conditions of the residual oil hydrogenation reaction were the same as those in Example 1. The hydrogenation effect is shown in Table 2.

[0072] Comparative Example 1

[0073] Weigh 3g of 120DU15 microspheres, the volume fraction of the hydrocarbon core to the volume fraction of the spherical shell of the thermoplastic acrylate polymer is 0.001%. Mix the microspheres with 100g of alumina dry powder and 120g of deionized water and knead them thoroughly. Put the kneaded materials into a high-temperature extruder capable of measuring, cooling and heating the material for extrusion molding. The temperature of the molding process is controlled to be 80°C to obtain alumina wet strips after pore expansion. Dry in an oven at 110°C at normal pressure for 2h, and after drying, calcine at 850°C for 3h to obtain an alumina carrier.

[0074] The pore volume of the alumina carrier is 0.91mL / g, pores with a pore diameter of 1 to 15nm account for 91.5%, pores with a pore diameter greater than 15nm account for 7.2% of the total pore volume, pores with a pore diameter greater than 15nm are mainly distributed in the range of 3μm to 12μm, and the pore volume of pores with a pore diameter of 3μm to 12μm accounts for 2.5% of the total pore volume. The mechanical strength of the carrier is 20N / mm, and the specific surface area is 125m 2 / g.

[0075] The alumina carrier is impregnated with an impregnation liquid containing active metals to obtain a hydrogenation catalyst. The hydrogenation catalyst contains 5wt% of molybdenum oxide and 2wt% of nickel oxide based on the mass of the carrier.

[0076] The above hydrogenation catalyst was applied to the residual oil hydrogenation reaction. The raw oil properties and hydrogenation reaction conditions of the residual oil hydrogenation reaction were the same as those in Example 1. The hydrogenation effect is shown in Table 2.

[0077] Comparative Example 2

[0078] Weigh 3g of 120DU15 microspheres, the volume fraction of the hydrocarbon core to the volume fraction of the spherical shell of the thermoplastic acrylate polymer is 0.001%. Mix the microspheres with 100g of alumina dry powder and 120g of deionized water and knead them thoroughly. Put the kneaded materials into a high-temperature extruder capable of measuring, cooling and heating the material for extrusion molding. The temperature of the molding process is controlled to be 200°C to obtain the alumina wet strips after pore expansion. Dry them in an oven at 110°C at normal pressure for 2h, and after drying, calcine them at 850°C for 3h to obtain the alumina carrier.

[0079] The pore volume of the alumina carrier is 0.91mL / g, pores with a pore diameter of 1 to 15nm account for 91.5%, pores with a pore diameter greater than 15nm account for 7.1% of the total pore volume, pores with a pore diameter greater than 15nm are mainly distributed in the range of 2μm to 10μm, and pores with a pore diameter of 2μm to 10μm account for 2.9% of the total pore volume. The mechanical strength of the carrier is 21N / mm, and the specific surface area is 126m 2 / g.

[0080] The alumina carrier is impregnated with an impregnation liquid containing active metals to obtain a hydrogenation catalyst. The hydrogenation catalyst contains 5wt% of molybdenum oxide and 2wt% of nickel oxide based on the mass of the carrier.

[0081] The above hydrogenation catalyst was applied to the residual oil hydrogenation reaction. The raw oil properties and hydrogenation reaction conditions of the residual oil hydrogenation reaction were the same as those in Example 1. The hydrogenation effect is shown in Table 2.

[0082] Comparative Example 3

[0083] Weigh 3g of 120DU15 microspheres, the volume fraction of the hydrocarbon core to the volume fraction of the spherical shell of the thermoplastic acrylate polymer is 10%. Mix the microspheres with 100g of alumina dry powder and 120g of deionized water and knead them thoroughly. Put the kneaded materials into a high-temperature resistant extruder that can measure, cool and heat the material for extrusion molding. The temperature of the molding process is controlled at 170°C to obtain wet alumina strips with expanded holes. Dry in an oven at 110°C at normal pressure for 2h. After drying, calcine at 850°C for 3h to obtain an alumina carrier. The alumina carrier obtained by extrusion has a fried strip phenomenon, an irregular shape, and visible millimeter holes on the surface. The mechanical strength of the carrier is 4N / mm. The specific surface area is 100m 2 / g.

[0084] The alumina carrier is impregnated with an impregnation liquid containing active metals to obtain a hydrogenation catalyst. The hydrogenation catalyst contains 5wt% of molybdenum oxide and 2wt% of nickel oxide based on the mass of the carrier.

[0085] The above hydrogenation catalyst was applied to the residual oil hydrogenation reaction. The raw oil properties and hydrogenation reaction conditions of the residual oil hydrogenation reaction were the same as those in Example 1. The hydrogenation effect is shown in Table 2.

[0086] Comparative Example 4

[0087] Weigh 3g of acrylonitrile-methacrylonitrile copolymer, 100g of alumina dry rubber powder and 120g of deionized water, mix and knead thoroughly, and put the kneaded materials into a high-temperature resistant extruder capable of measuring, cooling and heating the materials for extrusion molding. The temperature of the molding process is controlled at 170°C to obtain alumina wet strips after pore expansion. Dry in an oven at 110°C at normal pressure for 2h, and after drying, calcine at 850°C for 3h to obtain an alumina carrier.

[0088] The pore volume of the alumina carrier is 0.90 mL / g, pores with a pore diameter of 1 to 15 nm account for 96.1%, pores with a pore diameter greater than 15 nm are mainly distributed in the range of 16 nm to 25 nm, and the pore volume of pores with a diameter of 16 nm to 25 nm accounts for 2.1% of the total pore volume. The mechanical strength of the alumina carrier is 24 N / mm. The specific surface area is 131 m 2 / g.

[0089] The alumina carrier is impregnated with an impregnation liquid containing active metals to obtain a hydrogenation catalyst. The hydrogenation catalyst contains 5wt% of molybdenum oxide and 2wt% of nickel oxide based on the mass of the carrier.

[0090] The above hydrogenation catalyst was applied to the residual oil hydrogenation reaction. The raw oil properties and hydrogenation reaction conditions of the residual oil hydrogenation reaction were the same as those in Example 1. The hydrogenation effect is shown in Table 2.

[0091] Table 1 Raw oil properties

[0092] nature Raw oil-Qilu mixed residual oil <![CDATA[Density (20 °C) / g·cm -3 > 0.9722 S / wt% 2.1 Ni / ppm 24.8 V / ppm 19.7

[0093] Table 2 Hydrogenation effect of the catalyst obtained in each example

[0094] Ni removal rate / % V removal rate / % Example 1 41 68 Example 2 45 78 Example 3 42 71 Example 4 40 69 Example 5 43 76 Example 6 44 78 Comparative Example 1 32 55 Comparative Example 2 30 53 Comparative Example 3 28 58 Comparative Example 4 32 55

[0095] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. An application of an alumina carrier in a hydrogenation catalyst, which is applied to the hydrodemetallization reaction of residual oil; The preparation method of the alumina carrier comprises the following steps: mixing the alumina dry rubber powder and the microsphere expansion agent uniformly, kneading, molding, drying and calcining to obtain the alumina carrier; The microsphere expansion agent has a core-shell structure, wherein the outer shell is a thermoplastic acrylic polymer and the inner core is a hydrocarbon; the outer shell of the microsphere expansion agent has a temperature resistance limit of 80-150°C; the initial volatilization temperature of the inner core hydrocarbon is 70-100°C; The volume fraction of the hydrocarbon in the inner core of the microsphere expansion agent to the outer shell volume is 0.0001% to 0.1%; The molding process should control the temperature to be 10°C to 50°C higher than the initial volatilization temperature of the microsphere expansion agent core; or, the molding process should control the temperature to be 5°C to 40°C higher than the temperature limit of the shell of the microsphere expansion agent; The weight of the added microsphere expansion agent is 2%~30% of the weight of the alumina dry glue powder; The alumina carrier has a bimodal pore structure with good permeability. The pore volume of the alumina carrier is 0.8-1.3 mL / g; the pore volume of pores with a pore diameter of 1-15 nm accounts for 40%-92% of the total pore volume; the pore volume of pores with a pore diameter of 50-900 nm accounts for 5%-59% of the total pore volume.

2. The application according to claim 1, characterized in that: The outer shell temperature limit of the microsphere expansion agent is 110-130°C; the initial volatilization temperature of the hydrocarbon in the inner core is 80-100°C.

3. The application according to claim 1, characterized in that: The volume fraction of the inner core hydrocarbon volume of the microsphere expansion agent to the outer shell volume is 0.0002% to 0.001%.

4. The use according to claim 1, characterized in that: The molding process should be carried out at a temperature that is 20°C to 40°C higher than the initial volatilization temperature of the microsphere expansion agent core.

5. The use according to claim 1 or 4, characterized in that: The molding process should control the temperature to be 10°C to 25°C higher than the shell temperature limit of the microsphere expansion agent.

6. The use according to claim 1, characterized in that: The microsphere expansion agent has the following properties: particle size is 10-20 μm; the initial volatilization temperature of the inner core is 85-95° C.; and the temperature resistance limit of the outer shell is 115-130° C.

7. The use according to claim 1, characterized in that: The weight of the added microsphere expansion agent is 3% to 15% of the weight of the alumina dry glue powder.

8. The use according to claim 1, characterized in that: The forming is extrusion forming.

9. The use according to claim 1, characterized in that: The drying is carried out at 50-150° C. for 1 h-5 h; and the calcining is carried out at 500-1000° C. for 2 h-5 h.

10. The use according to claim 9, characterized in that: The calcination temperature is 800-1000°C.

11. The use according to claim 1, characterized in that: The mechanical strength of the alumina carrier is 10-50 N / mm.

12. The use according to claim 1, characterized in that: The mechanical strength of the alumina carrier is 10-40 N / mm.

Citation Information

Patent Citations

  • Preparation method of macroporous alumina carrier

    CN102861615B

  • Process for preparation of catalyst carrier and its use in catalyst preperation

    CN101237926A

  • Process for preparation of a catalyst carrier

    CN101237927A